Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae) - Qian, Hongge; Bai, Xiaoshuan; Heiss, Ernst; Liu, Aiping; Cai, Wanzhi (Zootaxa, 2019)
A new apterous genus, Rotundocoris gen. nov., and two included new species, R. stenonotum sp. nov. and R. obliquonotum sp. nov. (Hemiptera: Heteroptera: Aradidae: Carventinae), are described from Hainan, China. The diagnostic morphological features of the genus and its two species are discussed and illustrated.